Spory wokół pojęcia najlepszej dostępnej techniki BAT w ekonomii środowiskowej - Czaja, Stanisław; Becla, Agnieszka (Discussions about the best available techniques (BAT) idea in the environmental economics, 2008)
The article presents the best available techniques’ (BAT) idea. BAT is playing very important role in the modern environmental economics. The BAT idea is associated with legal, technical, economical and ecological problems. The European Community prepared some adequate organizational and legal solutions. The BAT idea immediate results from IPPC Directive. The realization of BAT idea is carrying some chances and threats and required some varied solutions. The authors present some of these problems.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 45-57